Anti-hacker tool kit - Shema, Mike (McGraw-Hill Education, 2014)
Fully revised to include cutting-edge new tools for your security arsenal, Anti-Hacker Tool Kit, Fourth Edition reveals how to protect your network from a wide range of nefarious exploits. You'll get detailed explanations of each tool's function along with best practices for configuration and implementation illustrated by code samples and up-to-date, real-world case studies. This new edition includes references to short videos that demonstrate several of the tools in action. Organized by category, this practical guide makes it easy to quickly find the solution you need to safeguard your system from the latest, most devastating hacks.